2016
DOI: 10.1186/s12934-016-0511-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an accurate kinetic model for the central carbon metabolism of Escherichia coli

Abstract: BackgroundA kinetic model provides insights into the dynamic response of biological systems and predicts how their complex metabolic and gene regulatory networks generate particular functions. Of many biological systems, Escherichia coli metabolic pathways have been modeled extensively at the enzymatic and genetic levels, but existing models cannot accurately reproduce experimental behaviors in a batch culture, due to the inadequate estimation of a specific cell growth rate and a large number of unmeasured par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 43 publications
1
40
1
Order By: Relevance
“…Kinetic models of these pathways have been developed to investigate carbon uptake and metabolism under aerobic conditions [1315, 17, 20]. Here, we constructed a kinetic model applicable under micro-aerobic (and anaerobic) conditions as well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic models of these pathways have been developed to investigate carbon uptake and metabolism under aerobic conditions [1315, 17, 20]. Here, we constructed a kinetic model applicable under micro-aerobic (and anaerobic) conditions as well.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed kinetic model of central carbon metabolism in E. coli that incorporates a constrained optimization method for parameter estimation on a supercomputer was recently developed [20]. As compared with other kinetic models, this model enabled more accurate prediction of the dynamics of wild-type (WT) cells and multiple-gene-knockout mutants in batch culture.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, different E. coli mutants have been developed to improve the conversion efficiency from glucose to L‐tryptophan (Chan, Tsai, Chen, & Mou, ; Ikeda, ; Wang et al, ; Zhao et al, ), and metabolic reaction pathways for bacterial L‐tryptophan synthesis have been identified in detail (Jahan, Maeda, Matsuoka, Sugimoto, & Kurata, ; Luo et al, ; Nishio et al, ). In addition, recent studies observed that acetate is excreted by E. coli during aerobic fermentation when the carbon flux into cells exceeds the capacity of the carbon central metabolic pathway (Dodge & Gerstner, ), which inhibits both cell growth and L‐tryptophan biosynthesis (Cheng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…What is more, to facilitate process design and optimization, it is essential to construct accurate kinetic models capable of simulating biomass growth, glucose uptake, and L‐tryptophan production in different scales of systems. However, in spite of the intensive modeling studies focused on the metabolic reaction network level (Jahan et al, ; Luo et al, ; Nishio et al, ), few attention has been paid to address this issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation